Forms of Control and Restriction in 20th century Novel - Blažková, Lucie (Univerzita Pardubice, 2012)
This paper is focused on British and American post-war literature, namely on 1984 by George Orwell and Fahrenheit 451 by Ray Bradbury. Both novels share many common features concerning gaining absolute power over society with the help of mass media, breaking relationships and manipulation. Two different forms of governance are brought to focus and the aim is to prove that both political strategies are equally effective in terms of subduing the society.
Formy kontroly a omezení v románech 20. století
Keywords: válka; moc; média; individualismus; manipulace; war; power; media; individualism; manipulation